(untitled) (Mustansiria Dental Journal, 2018)
Zamzam water has scientifically been proven to contain high concentration of calcium, magnesium, fluoride and many other minerals. This study aimed to test the ability of zamzam water to increase the resistance of enamel surface against acid dissolution compared to sodium fluoride. Teeth sample of 15 maxillary first premolars were randomly divided into 3 groups, study group treated with zamzam water, control positive treated with sodium fluoride and control negative treated with deionized water. The treatment lasted for two minutes once daily for 20 days interval. Then the concentration of the dissolved calcium ion in the etching solution of 2N HCl was measured by flame atomic absorption spectrometer. The amount of the released calcium ion from zamzam water treated group was lesser than that released from sodium fluoride treated group. However the difference was statistically not significant. A highly significant more calcium was dissolved from the water control group compared with the mentioned agents P<0.01. Zamzam water effectively increase tooth resistance against acid dissolution, therefore it is useful to harden enamel surface against dental caries challenge.